Dan Shen (Salvia miltiorrhiza) in Medicine Volume 3. Clinical Research - Yan, Xijun (Springer Netherlands : Imprint: Springer, 2015)
This book reviews research on Dan Shen, compiles data from clinical trials and biological experiments, and summarizes the latest research advances. It covers the medicinal herb, herbal pieces, and new proprietary drugs that contain it; it also covers simple and compound, traditional and contemporary formulas, and addresses a broad range of subjects, including: standardized cultivation; biodiversity; effective substances and their biological activities; quality control; and clinical trials. The book goes on to present the clinical trials on Dantonic, especially focusing on its therapeutic effects for coronary heart disease. It discusses compound prescriptions and compatibilities, from the herbal piece level to composition level, and describes approaches to research on modern Chinese medicine.   Volume 1 describes the biology and chemistry of Dan Shen, while Volume 2 focuses on pharmacology and quality control. Volume 3 describes the clinical research on Dan Shen.   Editor Xijun Yan is the President of Tianjin Tasly Group and a Member of the TCM Standardization Technical Committee. Gathering contributions from more than 100 authors working in the field of pharmaceutical and clinical research, the book presents and analyzes the available information from multiple aspects, reflects the current status of Dan Shen research, and offers an essential reference work for further research and development.